2016
DOI: 10.1016/j.jcs.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of commercial (α-type) zein with hydrogen peroxide improves its hydration and dramatically increases dough extensibility even below its glass transition temperature

Abstract: To improve the rheological properties of zein doughs, α-type zein and zein-starch doughs were prepared with the oxidising agents, hydrogen peroxide and peroxidase, which strengthen gluten-based doughs by cross-linking. Hydrogen peroxide and peroxidase increased zein dough extensibility compared to preparation with water. Hydrogen peroxide prepared zein doughs were extensible and cohesive below zein's glass transition temperature.The doughs did not exude water and maintained flexibility when stored. Confocal la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…However, the data shows that the presence of acetic acid in commercial zein dough made it far more extensible than when water alone was used. This is similar to the effect of commercial zein dough preparation with hydrogen Figure 4: Representative stress-strain curves of the effects of zein type, film formation and rinsing residual glacial acetic acid out with distilled water on zein doughs made with distilled water or 1.3% (w/w) acetic acid peroxide (Taylor et al, 2016a). Like zein dough preparation with hydrogen peroxide, this is as result of formation of continuous fibrils (Figure 3) as was previously found by Sly et al (2014) with commercial zein dough prepared with dilute organic acids.…”
Section: Tensile Properties Of α-Zein and Total Zein Doughssupporting
confidence: 60%
See 1 more Smart Citation
“…However, the data shows that the presence of acetic acid in commercial zein dough made it far more extensible than when water alone was used. This is similar to the effect of commercial zein dough preparation with hydrogen Figure 4: Representative stress-strain curves of the effects of zein type, film formation and rinsing residual glacial acetic acid out with distilled water on zein doughs made with distilled water or 1.3% (w/w) acetic acid peroxide (Taylor et al, 2016a). Like zein dough preparation with hydrogen peroxide, this is as result of formation of continuous fibrils (Figure 3) as was previously found by Sly et al (2014) with commercial zein dough prepared with dilute organic acids.…”
Section: Tensile Properties Of α-Zein and Total Zein Doughssupporting
confidence: 60%
“…Furthermore, recent work concerning the reasons for zein's viscoelasticity with respect to formation of a β-sheet conformation (Erickson et al, 2012) and improvement of zein dough properties using dilute acetic acid and lactic acids (Sly et al, 2014) or the oxidising agent hydrogen peroxide (Taylor et al, 2016a) have shown promise. However, to date virtually all research on zein dough functionality has involved using preparations comprising essentially only the α-zein class (Taylor et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…However, no direct evidence has been presented. With regard to direct effects of oxidizing agents on commercial zein (which largely lacks γ‐zein), it has been found that “dough” preparation in the presence of hydrogen peroxide greatly enhances the resulting extensibility of zein viscoelastic masses (Taylor, Johnson, Taylor, Njila, & Jackaman, ). This finding was attributed to hydroxylation of aliphatic amino acid side chains in zein through oxidation by the hydrogen peroxide.…”
Section: Physical and Chemical Modification Of Kafirin To Improve Funmentioning
confidence: 99%
“…Perhaps, surprisingly, in view of the well‐described effects of cross‐linking on kafirin film properties (“Different Solvents,” “Plasticization,” “Chemical Cross‐Linking,” and “Enzymic Cross‐Linking”), there is a dearth of research into the effects of oxidants on the functional properties of kafirin and zein bioplastics. With cast films made from commercial zein, Taylor, Johnson, et al () showed that treatment of the zein with hydrogen peroxide did not cause evident disulfide‐ or other covalent‐bond‐mediated polymerization of the zein. However, film‐water uptake was enhanced.…”
Section: Physical and Chemical Modification Of Kafirin To Improve Funmentioning
confidence: 99%
“…Additional research found that zein doughs prepared with hydrogen peroxide added showed increased extensibility and had the ability to remain extensible below the glass transition of zein (J.R.N. Taylor, Johnson, Taylor, Njila, & Jackaman, ), which was significant as handling of untreated zein dough below T g resulted in destruction of zein fibrils, loss of dough functionality, and poor bread quality (Lawton, ; Schober et al., ).…”
Section: Introductionmentioning
confidence: 99%